Urgent care emergencies : avoiding the pitfalls and improving the outcomes - Goyal, Deepi; Mattu, Amal. (Chichester, West Sussex, England ; Hoboken, NJ : Wiley-Blackwell, 2012)
This text was developed to help providers who evaluate low acuity complaints in any setting. The aim is to highlight common pitfalls in the management of those seemingly minor illnesses or injuries, which if not identified early or if managed incorrectly can have devastating and longterm consequences. This text will bring the provider's attention to high-risk aspects of chief complaints that may be encountered in a variety of low-acuity settings. Focused on high-risk pitfalls practitioners may encounter in everyday practice, each of the book's chapters is written by an expert chosen for his.
HEENT pitfalls / Alisa M. Gibson and Sarah K. Sommerkamp -- Management of genitourinary complaints / George Willis and Nadia Eltaki -- Orthopedic pitfalls of the upper extremity / Brooks M. Walsh and Reinier van Tonder -- Orthopedic pitfalls of the lower extremity / Christopher S. Kiefer -- Orthopedic pitfalls : pediatrics / Jana L. Anderson and James L. Homme -- Pitfalls of wound management / Michael K. Abraham and Hyung T. Kim -- Emergency dermatology for the acute care provider / Eric T. Boie and Jennifer A. Lisowe -- Management of common infections / Siamak Moayedi and Mercedes Torres -- Headache / Michael J. Laughlin Jr. and David M. Nestler -- The evaluation and management of back pain / Michael C. Bond -- Pediatric pitfalls / Jana L. Anderson and James L. Homme -- Geriatric pitfalls / Joseph P. Martinez -- Pharmacology pitfalls and pearls in urgent care medicine / Christopher E. Anderson and Ronna L. Campbell -- Talking the talk : effective communication in urgent care / Stephen Schenkel.
Includes bibliographical references and index.
Print version record.
Keywords: Ambulatory medical care; Medical emergencies; Emergencies; HEALTH & FITNESS -- Diseases -- General; HEALTH & FITNESS -- Health Care Issues; MEDICAL -- Diseases; MEDICAL -- Health Care Delivery; MEDICAL -- Health Policy; MEDICAL -- Public Health; SOCIAL SCIENCE -- Disease & Health Issues; Ambulatory medical care; Emergencies; Medical emergencies; Ambulatory Care; Emergencies; Treatment Outcome; Electronic books; Electronic books